The Varieties of Self-Transcendent Experience. Issue 2 (June 2017) - Yaden, David Bryce; Haidt, Jonathan; Hood, Ralph W.; Vago, David R.; Newberg, Andrew B.
Various forms of self-loss have been described as aspects of mental illness (e.g., depersonalization disorder), but might self-loss also be related to mental health? In this integrative review and proposed organizational framework, we focus on self-transcendent experiences (STEs)—transient mental states marked by decreased self-salience and increased feelings of connectedness. We first identify common psychological constructs that contain a self-transcendent aspect, including mindfulness, flow, peak experiences, mystical-type experiences, and certain positive emotions (e.g., love, awe). We then propose psychological and neurobiological mechanisms that may mediate the effects of STEs based on a review of the extant literature from social psychology, clinical psychology, and affective neuroscience. We conclude with future directions for further empirical research on these experiences.